Educational model transition: Student evaluation of teaching amid the COVID-19 pandemic - Campos, Esmeralda; Daruich, Sandra Dennis Núñez; de la O, Jose Francisco Enríquez; Castaño, Raquel; Escamilla, Jose; Hosseini, Samira (Frontiers in Education, 2022)
The Education 4.0 Framework calls for Higher Education Institutions (HEIs) to innovate their curriculum for developing the competencies of the future. Tecnologico de Monterrey started a transition from an active-learning educational model to Tec21, a challenge-based learning educational model focused on competency development. After one semester of this transition, the COVID-19 pandemic disrupted education worldwide, causing most universities to adapt to online education. We found the opportunity to analyze the institutional Student Evaluation of Teaching (SET) survey at different stages of the COVID-19 pandemic, prior to the outbreak, in the transition to online learning, and after the transition to fully online course delivery. We performed this analysis separately for the two coexisting educational models and each of the schools at the university. We also compared the SET scores for the spring semester of 2021, when the two educational models had a comparable number of students. We found that SET scores were not negatively impacted by the COVID-19 pandemic hinting towards positive implications about the institutional response to the pandemic. Another finding is that the Tec21 educational model has received higher SET scores, which implies a positive perception by students. There were a few exceptions to these results, which we address explicitly; for instance, the COVID-19 pandemic might have affected SET scores in the School of Medicine and Health Sciences. Further research is necessary to evaluate the implementation of the Tec21 model comprehensively.